Identification and functional analysis of novel genes expressed in the Anterior Visceral Endoderm - Goncalves, Lisa (2016)
During early vertebrate development, the correct establishment of the body axes is critical. The anterior pole of the mouse embryo is established when Distal Visceral Endoderm (DVE) cells migrate to form the Anterior Visceral Endoderm (AVE). Symmetrical expression of Lefty1, Cer1 and Dkk1 determines the direction of DVE migration and the future anterior side. In addition to the establishment of the Anterior-Posterior axis, the AVE has also been implicated in anterior neural specification. To better understand the role of the AVE in these processes, we have performed a differential screening using Affymetrix GeneChip technology with AVE cells isolated from cer1P-EGFP transgenic mouse embryos. We found 175 genes which were upregulated in the AVE and 36 genes in the Proximal-posterior sample. Using DAVID software, we characterized the AVE cell population regarding cellular component, molecular function and biological processes. Among the genes that were found to be upregulated in the AVE, several novel genes were identified. Four of these transcripts displaying high-fold change in the AVE were further characterized by in situ hybridization in early stages of development in order to validate the screening. From those four selected genes, one, denominated Adtk1, was chosen to be functionally characterized by targeted inactivation in ES cells. Adtk1 encodes for a serine/threonine kinase. Adtk1 null mutants are smaller and present short limbs due to decreased mineralization, suggesting a potential role in chondrogenesis during limb development. Taken together, these data point to the importance of reporting novel genes present in the AVE.